Auditing investment contracts and its reflection on sustainable development: (Applied Research in general contracting company) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Investment contracts are one of the state contracts concluded with the foreign private person in the field of investment in order to advance economic and social development programs, bring technical and practical expertise, create job opportunities and encourage investments. For this reason, the research aims to demonstrate the importance of the role of auditing investment contracts and its impact on sustainable development, especially after 2003, as successive governments in Iraq sought to enable the private sector to intervene in regulating the reality of public services provided to citizens, due to the change in political thinking and democratic development in governance policy that cast a shadow on The way the state is administered and the extent to which government institutions control the task of providing public services to citizens, and despite the existence of a set of laws before 2003 that governed many sectors, the shift in the policy of the regime allowed the private sector to invest in many areas that were monopolized by official institutions , After 19 years have passed since this transformation, it has become necessary for us, as researchers, to study this transformation accurately and seriously, and the extent to which this transformation is appropriate to the Iraqi reality. Investment paragraphs in accordance with the goals of sustainable development.